1985
DOI: 10.1161/01.res.57.2.304
|View full text |Cite
|
Sign up to set email alerts
|

Renal nerve stimulation causes alpha 1-adrenoceptor-mediated sodium retention but not alpha 2-adrenoceptor antagonism of vasopressin.

Abstract: Renal alpha 2-adrenoceptor stimulation by epinephrine infusion reverses cyclic adenosine monophosphate-mediated effects of vasopressin on sodium and water excretion. We used this response to determine whether renal nerve stimulation can activate renal alpha 2-adrenoceptors in the non-recirculating isolated perfused rat kidney (Krebs-Henseleit solution; 3.5 g/100 ml Ficoll; 1 g/100 ml albumin; 36 degrees C; propranolol 100 nM). In the presence of alpha 1-adrenoceptor blockade with prazosin (30 nM) alpha 2-adren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 26 publications
5
28
0
1
Order By: Relevance
“…This relationship is by no means proven by the present studies; however, it is recognised that the major reabsorption pathway for calcium ions at these sections of the nephron is via the sodium/potassium ATPase-driven sodium/calcium counter transporter system at the basolateral membranes of the tubular cells (Katz, 1986 The results of the present study also indicated that x1-adrenoceptors were necessary for the activation of tubular sodium reabsorption as renal nerve stimulation in the presence of prazosin did not change sodium output whereas during administration ofidazoxan the magnitude of the increases in tubular sodium reabsorption were similar to those in the animals receiving only saline. A role for a1-adrenoceptors in the adrenergic stimulation of tubular sodium reabsorption in the rat was recently reported in in vitro studies by Smyth et al (1985) and the present study using in vivo experiments support these in vitro findings. It is becoming apparent that this particular end-point of adrenergic activity within the kidney also requires ax-adrenoceptors in the rabbit (Hesse & Johns, 1984a; and the dog (Osborn et al, 1983).…”
Section: Discussionsupporting
confidence: 90%
“…This relationship is by no means proven by the present studies; however, it is recognised that the major reabsorption pathway for calcium ions at these sections of the nephron is via the sodium/potassium ATPase-driven sodium/calcium counter transporter system at the basolateral membranes of the tubular cells (Katz, 1986 The results of the present study also indicated that x1-adrenoceptors were necessary for the activation of tubular sodium reabsorption as renal nerve stimulation in the presence of prazosin did not change sodium output whereas during administration ofidazoxan the magnitude of the increases in tubular sodium reabsorption were similar to those in the animals receiving only saline. A role for a1-adrenoceptors in the adrenergic stimulation of tubular sodium reabsorption in the rat was recently reported in in vitro studies by Smyth et al (1985) and the present study using in vivo experiments support these in vitro findings. It is becoming apparent that this particular end-point of adrenergic activity within the kidney also requires ax-adrenoceptors in the rabbit (Hesse & Johns, 1984a; and the dog (Osborn et al, 1983).…”
Section: Discussionsupporting
confidence: 90%
“…29 Others have demonstrated that sympathetic nerve endings directly release norepinephrine on renal epithelial cells and can cause a 30% to 40% increase in sodium and water reabsorption via α-1 adrenergic receptors even before any hemodynamic changes could be detected. 30,31 …”
Section: Renal Nerves: Efferent and Afferent Sympathetic Fibersmentioning
confidence: 99%
“…In our study, it was unlikely that idazoxan was a partial al-adrenoceptor agonist. This would be expected to decrease urine flow rate and sodium excretion (Smyth et al, 1985) and not increase these parameters as we observed. Goldstein et al (1983) using doses similar to that reported in the present study found that, whereas low doses (0.25 mg kg-') of RX 781094 (idazoxan) suppressed nerve firing in the locus coeruleus, a slightly higher dose (1.0 mg kg-1) increased the firing rate.…”
Section: Resultsmentioning
confidence: 50%